2005
DOI: 10.1016/j.rmed.2004.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Technical description of endoscopic ultrasonography with fine-needle aspiration for the staging of lung cancer

Abstract: EUS-FNA is minimally invasive, accurate, and fast. Anatomical areas can be reached that are inaccessible for cervical mediastinoscopy. EUS-FNA is useful for the staging of lung cancer or the assessment and diagnosis of abnormalities in the posterior mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Stations 8 and 9 can only be sampled by EUS, also, station 5 is easier to sample by EUS than by EBUS (14,15). Besides this, the easily sampled stations 2R and 4R by EBUS-TBNA can be seen with EUS; however sampling these stations is sometimes difficult because of their distant location (16,17). In a recent trial analyzing false negative results by EBUS-TBNA, EUS-FNA and combined procedure, the investigators found the false negative results of 23.8%, 28.6% and 14.7% per nodal station basis, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…Stations 8 and 9 can only be sampled by EUS, also, station 5 is easier to sample by EUS than by EBUS (14,15). Besides this, the easily sampled stations 2R and 4R by EBUS-TBNA can be seen with EUS; however sampling these stations is sometimes difficult because of their distant location (16,17). In a recent trial analyzing false negative results by EBUS-TBNA, EUS-FNA and combined procedure, the investigators found the false negative results of 23.8%, 28.6% and 14.7% per nodal station basis, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…After the patient was sedated using a combination of midazolam and pentazocine, the echoendoscope was advanced to the stomach, and the left adrenal gland, celiac region and left lobe of the liver were observed. The echoendoscope was then gradually withdrawn to the esophagus, and the following regions were evaluated: pulmonary ligament, paraesophageal, subcarinal, lower paratracheal, subaortic and upper paratracheal [25]. After the initial orientation, LNs larger than 5 mm across the short axis were intended for FNA.…”
Section: Methodsmentioning
confidence: 99%
“…EUS-FNA was performed in an out-patient setting under local anesthesia (with or without moderate sedation) using the curved linear scanning ultrasound endoscope (GF-UCT160-OL5; Olympus, Aartselaar, Belgium) connected to the ultrasound unit (Aloka, Mechelen, Belgium) (10), with monitoring of heart rate and oxygen saturation (16). Punctures were performed with a 22-gauge fine needle (EUS-needle; Olympus).…”
Section: Eus-fnamentioning
confidence: 99%